2010
DOI: 10.1172/jci41078
|View full text |Cite
|
Sign up to set email alerts
|

PINCH1 regulates Akt1 activation and enhances radioresistance by inhibiting PP1α

Abstract: Tumor cell resistance to ionizing radiation and chemotherapy is a major obstacle in cancer therapy. One factor contributing to this is integrin-mediated adhesion to ECM. The adapter protein particularly interesting new cysteine-histidine-rich 1 (PINCH1) is recruited to integrin adhesion sites and promotes cell survival, but the mechanisms underlying this effect are not well understood. Here we have shown that PINCH1 is expressed at elevated levels in human tumors of diverse origins relative to normal tissue. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 94 publications
(122 citation statements)
references
References 54 publications
4
117
0
1
Order By: Relevance
“…It has been reported that PINCH-1 protects tumour cells from Bax-dependent apoptosis through phosphorylation and activation of ERK1/2 and AKT or by downregulating expression and phosphorylation of the pro-apoptotic protein Bim (Chen et al, 2008;Eke et al, 2010). To test whether this is also occurring in PrE cells, we determined the phosphorylation levels of ERK1/2 and AKT in WT and PINCH-1 2/2 PrE cells cultured for 24 or 48 hours on FN.…”
Section: Loss Of Pinch-1 Leads To Increased Jnk Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that PINCH-1 protects tumour cells from Bax-dependent apoptosis through phosphorylation and activation of ERK1/2 and AKT or by downregulating expression and phosphorylation of the pro-apoptotic protein Bim (Chen et al, 2008;Eke et al, 2010). To test whether this is also occurring in PrE cells, we determined the phosphorylation levels of ERK1/2 and AKT in WT and PINCH-1 2/2 PrE cells cultured for 24 or 48 hours on FN.…”
Section: Loss Of Pinch-1 Leads To Increased Jnk Activationmentioning
confidence: 99%
“…PINCH-1 can bind several actin modulating proteins (Legate et al, 2006;Wickström et al, 2010), the Ras suppressor protein 1 (RSU-1) and the protein phosphatase 1a (PP1a). The latter two interactions were shown to modulate MAPK and phosphoinositol 3-kinase (PI3K)/AKT signalling, respectively (Masuelli and Cutler, 1996;Dougherty et al, 2008;Eke et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative possibility is that ILK and ILKinteracting protein(s) regulate oncogenic kinases by controlling the activity of phosphatases. This has been shown for Pinch-1, which binds to and inhibits protein phosphatase 1a (PP1a) resulting in sustained PKB phosphorylation and activity (Eke et al, 2010). Consequently, reducing the amounts of the IPP complex in FAs will concomitantly result in an increased PP1a activity and decreased PKB function.…”
Section: The Kinase Controversymentioning
confidence: 94%
“…Many potential PP1 regulatory partners have been found. Besides tensin (Eto et al 2007), PINCH1 has recently been identified as a regulator of PP1a in FAs (Eke et al 2010). PINCH is a constitutive component of the integrin-linked kinase, PINCH, and parvin (IPP) complex (Legate et al 2006).…”
Section: Phacr4 Regulates Integrin Signaling Genes and Developmentmentioning
confidence: 99%